USING ANTHROPOMETRIC DATA TO DESIGN A FORTABLE STUDY DESK AND USER POSTURE ANALYSIS WITH THE RAPPID UPPER LIMB ASSESSMENT (RULA) METHOD - Yuyun Yuniar Rohmatin; Nurjannah Nurjannah; Stephanus Benedictus (International Journal Science and Technology, 2023)
The use portable study desk that is designed to be easy moved still make complaints in muscles and bones give risk for posture. Design improvements can be based on measurementsÂ  results of static anthropometric and dynamic anthropometric to identify the risk of posture. The method used in this reaserch is a Rapid Upper Limb Assessment (RULA) method to analyze the risk of posture users of portable study desk, while for the design of study desk using anthropometric data, The purpose of this study was to design a portable study table and analyze the risk posture that occur when users use a portable study desk using the RULA method. The results of study show that design desk study using anthropometric data obtained dimensions of 800 mm in length and 420 mm in width. The table height from the floor to the table surface is 220 mm high. a place to put a D100 mm glass, and there is a place to put a 400 mm cell phone or iPad along with a hole for the cable, there is a Diameter 40 mm. The 2-dimensional and 3-dimensional design process uses Catia software. The results of the Rapid Upper Limb Assessment (RULA) analysis show that the user's posture risk is indicated in green color, which means that there is no posture that needs to be corrected and that posture is acceptable except for the posture muscles (muscles) which are are indicated red color so needed move as soon possible or muscle stretching, this is in line with Osha (2020) who states that static postures are recommended for stretching muscles to avoid muscle fatigue.